Quality of ram semen in relation to scrotal size - Sharmin, S; Islam, MM; Saha, A; Akter, S; Juyena, NS; Bari, FY (Bangladesh Veterinarian, 2022)
Aim of this study was to select superior rams by assessing their scrotal size and quality of semen. In ten indigenous Bangladeshi rams, the body weight, scrotal circumference, and scrotal volume of rams increased with age (P<0.05). Body weight at 381-410 days (13.6 ± 1.5 kg) was higher than at 169-200 days (10.2 ± 0.1 kg) and 201-230 days (10.4 ± 1.2 kg) (p<0.05). Scrotal circumference at 381 - 410 days (19.1 ± 0.3 cm) was higher (p<0.05) than at 169 - 200 days (17.2 ± 0.1 cm), 201 - 230 days (17.2 ± 0.6 cm), and 231 - 260 days (17.2 ± 0.5 cm). At 381 - 410 days, scrotal volume (87.4 ± 5.5 cm3) was higher than in the five youngest groups (p<0.05). Both scrotal circumference and volume were positively correlated (R2=0.519) with the increased body weight. Semen volume increased with age, which varied from 0.4 ± 0.0 - 1.2 ± 0.3 ml. The semen volume at 381 - 410 days (1.2 ± 0.3 ml) was higher than other age groups (P<0.05) except for 351 - 380 days. The mass activity of sperms of different age groups varied from 2.8 ± 0.4 to 4.3 ± 0.3. Sperm concentration, progressive motility (%), and normal spermatozoa (%) improved progressively with age, but significant changes in these parameters were seen when the animals reached 291 days or more (P<0.05). However, normal spermatozoa (%) improved from the age of 261 days. The mass activity was positively correlated with sperm concentration (R2 = 0.568) and with progressive motility (%) (R2 = 0.616). Measurements of scrotum could provide a reliable guide in estimating sperm production capacity, which are important for breeding soundness evaluation, and genetic improvement of indigenous rams. Bangl. vet. 2021. Vol. 38, No. 1-2, 1–9